Cost accounting : traditions and innovations - Barfield, Jesse T.; Rainborn, Cecily A.; Kinney, Michael R. (Cincinnati, OH : South-Western College, 2001)
This book is divided into five parts: Overview; Systems and methods of product costing; Planning and controlling; Decision making; and Evaluating performance.
Keywords: Accounting; Finance; Economics; Cost accounting